O tempo no Livro XI das Confissões de Agostinho - Fernandes, Hélton Pimenta (2026)
Much research and academic debate has focused on the question of time in Book XI of Augustine’s Confessions. Through biographical research and a close study of Book XI, this work seeks to show that Augustine approaches the question of time in a broad and profound way, discussing and highlighting a range of possible interpretations of this problem. In addition to examining the theme with all the depth available to him, Augustine proposes in this book a new understanding of time: a “moving forward” according to intentio, in contrast with the historically lived time that proceeds according to distentio. This new time—understood as an eschatological time—corresponds to a new identity characterized as that of a perfect traveler, a pilgrim journeying toward the Heavenly Jerusalem, grounded in conversion. It is not the perfect identity found in eternity, but rather a new time understood as a historical movement in the life of the soul, whose entire intentio is eschatologically directed toward God, and distinct from the time lived according to distentio, through which the soul becomes fragmented and dispersed among temporal realities. Conversion inserts the person into a new eschatological time in which all intentio is directed toward the things that are yet to come in eternity. This new time is not subjectivist but is shared by all whose love is directed toward God